Methodology of Quranic Interpretation in Faidur Rahman by KH. Saleh Darat - Siti Kusrini (Tafhim Al-'Ilmi, 2022)
Abstract Kyai Saleh Darat is a scholar who wrote about 12 books in Javanese with Arabic pegon, one of which is Faidh ar-Rahman, several personal opinions of Kyai Saleh are able to describe the characteristics of his interpretation of the Koran. This is what researchers describe more broadly. The researcher uses descriptive qualitative methods with a hermeneutic approach through the book Faid ar-Rahman fi Tarjamah Tafsir Kalam Malik ad-Dayyan. The commentary was written at RA Kartini's insistence during the recitation at the house of the Demak regent, Ario Hadiningrat. He used Arabic pegon to trick the Dutch colonialists, besides that why he used Arabic pegon, because the knowledge of Arabic for the common people was limited. This interpretation uses the shades of isyari and tasawuf. And in Saleh Darat's interpretation, many are relevant to be applied in the present. Keywords: Qur’an Interpretation, Faidh ar-Rahman, Saleh Darat